Особливості реалізації топосів свята та маски в східнослов’янському постмодернізмі (на матеріалі російської та української прози) - Шавокшина, Н. (Літературознавчі обрії. Праці молодих учених, 2010)
Sharing the ideas of close relations between Russian and Ukrainian postmodern literatures, which stipulate for the possibility to be viewed as the specific West Slavonic variant of postmodernism, the author investigates the differences in the ways of carnival tradition actualization in these literatures by analyzing the means of structuring carnival concepts of feast and mask realization in Russian and Ukrainian postmodernist prose.